Strategi pemanfaatan Palm Oil Mill Effluent (POME) sebagai sumber energi berkelanjutan di pabrik kelapa sawit PT. Meridan Sejati Surya Plantation Kabupaten Siak - Antoni Antoni; Yusni Ikhwan Siregar; Suwondo Suwondo (Pelantar Press, 2020)
The development of the palm oil industry in Indonesia is growing rapidly, including the increasing number of palm oil processing factories and their liquid waste which has an impact on increasing the amount of greenhouse gases through methane gas. This research was conducted to determine the strategy in utilizing the effluent palm oil mill as a sustainable energy source in the palm oil mill of PT. MSSP of Siak Regency. Utilization of palm oil mill effluent as biogas fuel is carried out using covered lagoon reactor pond technology and serves to reduce the emission value of 1,365.90 tons of CH4 during 2019 and to function in economic efficiency from the use of sustainable energy or biogas for companies by Rp. 8,109,598,450 and socially functioning for employees and the community around PT. MSSP is a positive perception, both in lightening the work of employees and reducing the will in community settlements. The strategy carried out in the utilization of palm oil mill effluent as a sustainable energy source at PT. MSSP aims at good and proper management and application. The strategy was formulated in the SWOT analysis by compiling strengths, weaknesses, opportunities and threats in the application of the utilization of palm oil mill effluent as a sustainable energy source.